DSP-ALGORITHMS FOR CARDIAC SYMPTOMS INVESTIGATIONS - Kalchev, Ivan (International Journal of Computing, 2014)
The achievements of the advanced medicine are not possible without the use of technical sciences. The aspiration for perfect instrumentation and for high precision of the technical systems for analysis of cardiac activity are still a challenge to engineers. The invention of more effective and with better quality indexes systems will permit a fast diagnostics, therefore a better medical treatment. In the present paper the main cardiac-vessel symptoms are described and an possible algorithm for program assurance of µP-system for cardiac investigations is proposed. The system is based on ADU 824 type of microprocessor, but the programs are compiled in MATLAB 4.2 environment.